INVESTIGATIONS ON THE CORN-STARCH MODIFIED LOW DENSITY POLYETHYLENE BLENDS - Oragwu, Ifeoma Perpetua (MATTER: International Journal of Science and Technology, 2016)
Investigations were carried out on the biodegradation properties of low-density polyethylene, modified with different concentrations by mass of corn-starch. Conventional Low-Density Polyethylene (LDPE) is widely used in all fields of life; therefore constitute the greatest municipal waste products, due to their inertness to biological attack, moisture, and weather conditions. Corn-starch which is a biofilter was characterized to ensure it’s suitability in the blending of synthetic plastics like LDPE. The percentage yield, moisture content, ash content, iodine test, etc were carried out on the extracted starch. The blended polyethylene sheets were injection molded at 150 0C after mixing 0, 2.50, 5.00, 7.50, 10.00, 12.50, and 15.00 wt. % by mass of the starch with a known weight of low-density polyethylene pellets. Mechanical tests and percentage weight-loss properties of the corn-starch modified low-density polyethylene were investigated before and after soil burial test. The evidence of biodegradation was exhibited on the reduced tensile strength, elongation at break, increased water absorption and other properties of the blended films as against the pure LDPE.